Synthetic, structural and reaction chemistry of N-heterocyclic germylene and stannylene compounds featuring N-boryl substituents - Kristinsdóttir, L; Oldroyd, N; Grabiner, R; Knights, A; Heilmann, A; Protchenko, A; Niu, H; Kolychev, E; Campos, J; Hicks, J; Christensen, K; Aldridge, S (Royal Society of Chemistry, 2019)
This study details the syntheses of N-heterocyclic germylenes and stannylenes featuring diazaborolyl groups, {(HCDippN)2B} (Dipp = 2,6-iPr2C6H3), as both of the N-bound substituents, with a view to generating electron rich and sterically protected metal centres. The energies of their key frontier orbitals - the group 14-centred lone pair and orthogonal pπ-orbital (typically the HOMO-2 and LUMO) have been probed by DFT calculations and compared with a related acyclic analogue, revealing (in the case of the stannylenes) a correlation with the measured 119Sn chemical shifts. The reactivity of the germylene systems towards oxygen atom transfer agents has been examined, with 2 : 1 reaction stoichiometries being observed for both Me3NO and pyridine N-oxide, leading to the formation of products thought to be derived from the activation of C-H bonds by a transient first-formed germanone.